Iron(ing) out parkinsonisms: The interplay of proteinopathy and ferroptosis in Parkinson's disease and tau-related parkinsonisms - Maria João da Costa Caiado; Amalia M. Dolga; Wilfred F.A. den Dunnen (Redox Biology)
Parkinsonian syndromes are characterised by similar motor-related symptomology resulting from dopaminergic neuron damage. While Parkinson's disease (PD) is the most prevalent parkinsonism, we also focus on two other variants, Progressive supranuclear palsy (PSP) and Corticobasal degeneration (CBD). Due to the clinical similarities of these parkinsonisms, and since definite diagnoses are only possible post-mortem, effective therapies and novel biomarkers of disease are scarce. Thus, we explore the current findings relating to the relationship of parkinsonism proteinopathy (α-synuclein in PD, and tau in PSP/CBD) paralleled to a specific form of cell death, ferroptosis. Ferroptosis is characterised by iron-induced lipid peroxidation and several markers of this pathway have been identified to control intracellular iron fluctuations. However, in parkinsonism, these mechanisms are thought to become dysfunctional. Although both proteinopathies have been linked to ferroptosis, much less is known about ferroptotic cell death and tau in the context of PSP/CBD. Interestingly, clinical trials targeting iron have recently shown conflicting results which begs to question the complexity of the ferroptotic pathway and alludes to the need for exploring other ferroptosis-related machinery as possible therapeutic targets. Overall, we address the literature gap in parkinsonism proteinopathy and ferroptosis, and its relevance to understanding disease pathophysiology and aetiology.